Evaluation of Kenaf/Polyester Fiber Blended Sliver Produced from Carding Machine - W. Mohd Rusli, N.; H. Abdul Rashid, A.; R. Ahmad, M.; M.N. Roslan, M.; Mohd Harun, D.; Che Ismail, S. (International Journal of Engineering and Technology, 2019)
Controlling sliver evenness is very important since this parameter can affect the quality of the yarn produced. In kenaf sliver production, kenaf fibres alone could not form a good sliver. Thus, fibres such as polyester are needed to blend with kenaf to improve fibre cohesiveness and form a better sliver. The aim of this study is to identify the optimum ratio of kenaf that can be used for sliver production. The heart of the process for the production of kenaf/polyester slivers is carding. The weight percentage of kenaf used for the kenaf/polyester sliver production was 50%, 60% and 70%. After sliver formation, the waste percentage, diameter and size were determined. The sliver images were analysed under video analyser and captured by digital SLR camera to observe the fibre blending. The research showed that lower percentage of kenaf offered better waste percentage and sliver diameter. Whereas, sliver size showed some decrement with an increment of kenaf fibre percentage. The presence of polyester in the production of kenaf/polyester sliver seems to play an important role to bind the kenaf fibres together.Â Â